Transcription factor Sp3 is silenced through SUMO modification by PIAS1 - Sapetschnig, Alexandra; Rischitor, Grigore; Braun, Harald; Doll, Andreas; Schergaut, Marion; Melchior, Frauke; Suske, Guntram (The EMBO journal, 2002)
Sp3 is a ubiquitous transcription factor closely related to Sp1. Here we show that Sp3 is a target for SUMO modification in vivo and in vitro. SUMO modification of Sp3 occurs at a single lysine located between the second glutamine-rich activation domain and the DNA-binding domain. Mutational analyses identified the sequence IKXE as essential for SUMO conjugation to Sp3. We identified the protein inhibitor of activated STAT1 (PIAS1) as an interaction partner of Sp3 and Ubc9. Moreover, PIAS1 strongly stimulated SUMO conjugation to Sp3, thus acting as an E3 ligase for SUMO conjugation to Sp3. All mutations that prevented SUMO modification in vitro strongly enhanced the transcriptional activity of Sp3, showing that SUMO modification silences Sp3 activity. SUMO-modified Sp3 bound to DNA with similar specificity and affinity as unmodified Sp3. However, DNA-bound Sp3 did not act as a substrate for SUMO modification.
Gesehen am 05.09.2023